2015
DOI: 10.1513/annalsats.201411-538oc
|View full text |Cite
|
Sign up to set email alerts
|

Counting Pyrazinamide in Regimens for Multidrug-Resistant Tuberculosis

Abstract: Mortality may be reduced by the inclusion of five likely effective drugs, including an injectable, during the intensive phase of treatment. If PZA is unlikely to be effective in an individual patient, these results suggest adding a different, likely effective drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
(30 reference statements)
2
13
0
Order By: Relevance
“…In the case of rifampin, a prior study found that phenotypic DST does not capture some clinically relevant resistance conferred by disputed rpoB mutations that had previously been considered of indeterminate significance; these were associated with a rate of failure or relapse of first-line retreatment of 63% (6). For pyrazinamide, only a few studies have directly evaluated the correlation between in vitro resistance with clinical outcomes (12,(29)(30)(31)(32). One of these reported that patients whose isolates had an MIC breakpoint of over 50 mg/liter had poor sputum conversion rates (12).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of rifampin, a prior study found that phenotypic DST does not capture some clinically relevant resistance conferred by disputed rpoB mutations that had previously been considered of indeterminate significance; these were associated with a rate of failure or relapse of first-line retreatment of 63% (6). For pyrazinamide, only a few studies have directly evaluated the correlation between in vitro resistance with clinical outcomes (12,(29)(30)(31)(32). One of these reported that patients whose isolates had an MIC breakpoint of over 50 mg/liter had poor sputum conversion rates (12).…”
Section: Discussionmentioning
confidence: 99%
“…[26] In contrast, the risk of mortality is nearly tripled when patients with pyrazinamide-resistant MDR-TB receive a regimen containing four likely effective drugs plus pyrazinamide that is not likely effective. [8] Since efficacy of treatment with pyrazinamide-containing regimens is compromised when pyrazinamide resistance is documented, pyrazinamide DST, even if imperfect, should guide regimen selection for patients with MDR-TB. [27] This is relevant to the current standard of care, including the recently endorsed shortened regimen and the conventional regimen, [9] as well as to new regimens under evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Questions have emerged about the utility of pyrazinamide in MDR-TB treatment when sensitivity to the drug is not confirmed. [7] The inclusion of pyrazinamide when M. tuberculosis bacilli are pyrazinamide resistant has been associated with higher risk of death, [8] and may be associated with unnecessary toxicity. Consequently, current WHO guidelines recommend that additional drugs should be included in MDR-TB regimens if the effectiveness of pyrazinamide or other core drugs may be compromised by resistance.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Treatment approaches for MDR-TB have shown that increasing the number of medications used is more successful than increasing the duration of treatment. [7][8][9] Current treatment regimens have not been able to reduce the number of MDR-TB and XDR-TB infections while achieving reductions in the number of TB infections and death. Despite all this knowledge and notable efforts, only two new anti-TB drugs, bedaquiline and delamanid, were approved for TB therapy in the last halfcentury.…”
Section: Introductionmentioning
confidence: 99%